Design and low energy ventilation solutions for atria in the tropics - Abdullah, Abd Halid; Fan Wang, Fan Wang (Elsevier, 2012)
A generic atrium building was designed to incorporate low energy solutions and features of both vernacular and contemporary South Asian architecture. To achieve low energy and comfort within the atrium space, some key design variables were examined by running a dynamic thermal model (DTM) for some representative cases. This DTM model was developed with multiple levels and zones to simulate the heat and air movement throughout the building and validated with the data measured in a real building of similar form. The modelling study was carried out to investigate the effects of two roof forms for the atrium and three low cost ventilation solutions on indoor thermal comfort. It reveals that low cost ventilation and acceptable comfort are achievable in this traditional form of architecture and low energy solutions and careful design can complement well its functional aspects and even enhance its aesthetic and practical qualities. The solar heat gain, air temperature, and mean radiant temperature in the atrium were used to assess the effectiveness of clerestory windows with opaque rooftop (i.e. side-lit model) as compared to the fully transparent glazed rooftop (i.e. top-lit model). Data on cooling loads, indoor air temperature, and mean radiant temperature were used to evaluate the design options with special consideration on local adaptable thermal comfort criteria. The possible effects of the research outcomes on the incorporation of atria are discussed at the end.